2007
DOI: 10.1016/j.pscychresns.2006.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in memory and static balance with abstinence in alcoholic men and women: Selective relations with change in brain structure

Abstract: We investigated whether changes in memory or static balance in chronic alcoholics, occurring with abstinence or relapse, are associated with changes in lateral and fourth ventricular volume. Alcoholics meeting DSM-IV criteria for Alcohol Dependence (n = 15) and non-alcoholic controls (n = 26) were examined twice at a mean interval of two years with standard Wechsler Abbreviated Scale of Intelligence (WASI), Wechsler Memory Scale-Revised (WMS-R) tests, an ataxia battery, and structural MRI. At study entry, alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 72 publications
4
70
1
1
Order By: Relevance
“…Human studies have provided substantial evidence that protracted abstinence results in improvement in neurocognitive function (Fein et al 2006; Sullivan et al 2000a; Sullivan et al 2000b), and induces structural changes in the brain (Carlen et al 1978; O’Neill et al 2001; Pfefferbaum et al 1995; Rosenbloom et al 2007). Thus, in the present study, AIE-induced neurodegeneration may have been partially recovered by the time behavioral testing began.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have provided substantial evidence that protracted abstinence results in improvement in neurocognitive function (Fein et al 2006; Sullivan et al 2000a; Sullivan et al 2000b), and induces structural changes in the brain (Carlen et al 1978; O’Neill et al 2001; Pfefferbaum et al 1995; Rosenbloom et al 2007). Thus, in the present study, AIE-induced neurodegeneration may have been partially recovered by the time behavioral testing began.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported poorer performance by alcoholics as compared to nonalcoholic controls in general cognitive abilities or intelligence (Sullivan et al, 2000b; Sullivan et al, 2002b; Davies et al, 2005; Rosenbloom et al, 2007), but the deficits have been mild, or they tended to improve within a year of abstinence (Bates et al, 2002). Other studies have reported no alcoholism-related impairments in general intelligence (Oscar-Berman et al, 2004; Fein et al, 2006; Foisy et al, 2007; Marinkovic et al, 2009; Sullivan et al, 2010; Pitel et al, 2012b).…”
Section: Profiles Of Damage and Repairmentioning
confidence: 99%
“…Despite decades of rigorous studies reporting regional cortical volume shrinkage and neuronal dysmorphology in vivo (Cardenas et al, 2011;Fein et al, 2009;Pfefferbaum et al, 2012;Zahr et al, 2011) and in postmortem tissue (Harper, 1998;Zahr et al, 2011), the question whether excessive alcohol consumption per se is the cause of these brain structural abnormalities remains unestablished. Although longitudinal neuroimaging studies provide compelling evidence for partial to complete reversal of observed brain tissue shrinkage or ventricular expansion with sobriety and progressive dysmorphology with continued drinking in humans (Cardenas et al, 2005;Pfefferbaum et al, 1995;Rosenbloom et al, 2007), such studies are constrained due to ethical and practical considerations when performed in human subjects and hence to their reliance on naturalistic observation. Thus, relevant factors, including premorbid assessment, environmental insult, nutritional deficiency, alcohol consumption patterns, comorbid psychopathology and other substance abuse, and the frequency of withdrawals cannot be controlled or often even adequately documented.…”
Section: Introductionmentioning
confidence: 99%